PERILAKU NELAYAN BAGAN IKAN TERI DI DESA LABUAN UKI KECAMATAN LOLAK KABUPATEN BOLAANG MONGONDOW - Andemora, Saputri Noveice; Matheosz, Jenny Nelly; Mamosey, Welly E. (HOLISTIK, Journal Of Social and Culture, 2021)
Marine resources are very helpful to the economy of Indonesian people, one of which is fishing. The majority of the people who made the arrests were people who lived in coastal areas. In general, coastal communities have a culture that is oriented in harmony with nature so that the technological system utilizes natural resources is adaptive technology with coastal conditions. To meet the needs of his life, the fishing community tries to catch as many fish as possible, both working during the day and night, both using machine technology equipment and traditional equipment.Each region has a culture in fishing, such as the culture of catching anchoated fish using bagan. In Labuan Uki Village, Lolak District of Bolaang Mongondow Regency, some people have livelihoods in the form of fishing in the sea. They have their own culture in fishing, namely by using boat bagan. Bagan is a fishing device that uses nets and lights so that it can be used for light anglers. The process of making boat bagan using various types of materials including bamboo, bagan nets and motorized boats that are at once as a means of transportation at sea. When the anchoated season arrives, the number of fish will be abundant and fishermen will sell anchoated fish to the market and be sold also to the collectors, but because of the large number of fish so that the fish will not sell out and there will still be many left and the rest is dried.Keywords: fisherman, bagan, anchoated